2019
DOI: 10.3390/ijms20215461
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of TFF1 and TFF3 in Patients Suffering from Chronic Rhinosinusitis with Nasal Polyposis

Abstract: Trefoil family factor (TFF) proteins contribute to antimicrobial defense and the maintenance of sinonasal epithelial barrier integrity. Dysregulation of TFF expression may be involved in the development of chronic inflammation and tissue remodeling characteristically found in chronic rhinosinusitis with nasal polyposis (CRSwNP). Expressions of TFF1 and TFF3 were determined in specimens of middle nasal turbinate (MNT-0), bulla ethmoidalis (BE), and nasal polyps (NP) from CRSwNP patients (n = 29) and inferior na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Previous work using immunostaining approaches demonstrated that TFF1 and TFF3 are associated with allergic rhinitis and CRSsNP, whereas TFF2 was largely undetectable 9, 25 . In addition, measuring TFF1 and TFF3 mRNA levels in the sinonasal mucosa of CRSwNP patients revealed a significant upregulation of TFF3 gene expression concomittant with downregulation of TFF1 gene expression 10 . TFF1 and TFF3 are known products of goblet cells in both healthy and inflamed sinonasal tissues, TFF3 was also produced by ciliated epithelial cells, and submucosal glandular cells 25, 26 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous work using immunostaining approaches demonstrated that TFF1 and TFF3 are associated with allergic rhinitis and CRSsNP, whereas TFF2 was largely undetectable 9, 25 . In addition, measuring TFF1 and TFF3 mRNA levels in the sinonasal mucosa of CRSwNP patients revealed a significant upregulation of TFF3 gene expression concomittant with downregulation of TFF1 gene expression 10 . TFF1 and TFF3 are known products of goblet cells in both healthy and inflamed sinonasal tissues, TFF3 was also produced by ciliated epithelial cells, and submucosal glandular cells 25, 26 .…”
Section: Discussionmentioning
confidence: 94%
“…In the context of CRS, increased gene expression levels for TFF1 and 3 in the sinonasal mucosa has been reported for the Type 1 associated CRSsNP subtype 9 . Moreover, increased TFF3 with concomittant decreased TFF1 gene expression levels in the sinonasal mucosa has been reported for the Type 2 associated CRSwNP subtype 10 . TFFs are expressed in healthy and diseased tissue in human and mouse models and correlate with disease severity in asthma and COPD 11, 12 .…”
Section: Introductionmentioning
confidence: 90%
“…Some of these genes (MUC5B, TFF1, and TFF3) were previously shown to be over-expressed in middle turbinate samples from patients with CRS. 39,40 (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Serous Cellsmentioning
confidence: 99%
“…Ciliated cells are responsible for mucociliary clearance. All airway secretory cell types differentiate from airway epithelial cells [ 23 , 24 , 25 ]. The airway mucus consists of a sol layer and a gel layer that together form a defense barrier termed the “cilia-mucus blanket” [ 26 , 27 ].…”
Section: The Biological Characteristics Of Mucinsmentioning
confidence: 99%